The Historicality and Purpose of Guardian Rules in Indonesian Islamic Family Legislation and Muslim Countries - Ach Syaifur Rizal; Samsul Arifin; Mawardi (Universitas Muhammadiyah Palu, 2023)
Marriage is one of the phases in life that a Muslim can live after finding his life partner. Marriage is not just lust, but establishes affection among families and creates peace in the family. If the family is peaceful and harmonious, a safe and secure family will be created. In a marriage, it is required to have a marriage guardian, whereas according to jumhur ulama, a marriage guardian is a condition and pillar of a valid marriage contract. If there is no marriage guardian, then the marriage is considered void. Meanwhile, other scholars argue that an adult woman may marry herself without having a marriage guardian, as long as she is married to a man who is equal (sekufu'). The two groups have the same clear foundation, both from the naqli argument and the aqli argument. In this debate, it is only limited to the debate of scholars, so researchers are interested in studying marriage guardians in the perspective of Indonesian state legislation and compared with the rules of world Muslim countries.